Hard seed breakdown pattern of sulla (Hedysarum coronarium L.) in relation to its regeneration capacity and persistence - Sulas L.; Re G.A.; Caredda S. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Sulla (Hedysarum coronarium L.) is a perennial legume characterized by a low persistence. In the year after sowing a double autumn regeneration mechanism can occur when seed has been set. In fact it regrows from previous year plants but also regenerates new seedlings from seed, like annual self-reseeding legumes. This research, carried out in Sardinia (Italy), was aimed to study and understand the hard seed breakdown pattern of sulla in relation to its regeneration and persistence. The first results of the year 1994-95 are reported in this paper.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)